2017
DOI: 10.1002/2016jb013637
|View full text |Cite
|
Sign up to set email alerts
|

Failure characteristics of two porous sandstones subjected to true triaxial stresses: Applied through a novel loading path

Abstract: We performed an extensive suite of true triaxial experiments in two porous sandstones, Bentheim (porosity ≈ 24%) and Coconino (17%). The experiments were conducted using a novel loading path, which maintains constant Lode angle (Θ) throughout the test. This path enabled the examination of the effects of Lode angle and mean stress on failure (σoct,f). Our tests covered σ3 magnitudes between 0 and 150 MPa and of Θ at −30° (axisymmetric extension), −16°, 0°, +11°, +21°, and +30° (axisymmetric compression). Test r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 51 publications
(153 reference statements)
0
16
0
Order By: Relevance
“…Moreover, a growing number of in situ stress measurements have indicated that axisymmetric stress conditions (like the ones applied in conventional triaxial tests) are rare in the Earth's crust. 81,88,89 Thus, conventional triaxial testing does not faithfully replicate typical crustal stress conditions (where σ 1 ≥ σ 2 ≥ σ 3 ). This constitutes the necessity of exploring the deformation and failure characteristics of flawed specimens under true triaxial compression.…”
Section: Crack Initiation and Growth In Flawed Rocks Under Triaxial Compressionmentioning
confidence: 99%
“…Moreover, a growing number of in situ stress measurements have indicated that axisymmetric stress conditions (like the ones applied in conventional triaxial tests) are rare in the Earth's crust. 81,88,89 Thus, conventional triaxial testing does not faithfully replicate typical crustal stress conditions (where σ 1 ≥ σ 2 ≥ σ 3 ). This constitutes the necessity of exploring the deformation and failure characteristics of flawed specimens under true triaxial compression.…”
Section: Crack Initiation and Growth In Flawed Rocks Under Triaxial Compressionmentioning
confidence: 99%
“…Since all the three principal stresses vary during the loading and unloading of the specimen, the octahedral shear stress τ oct in Equation ( 3) is used to generalize the strength characteristic of the specimen [33]:…”
Section: Characteristics Of Strength and Deformationmentioning
confidence: 99%
“…This leaves the prediction of the structural behavior and performance of sandstone as a significant challenge. Consequently, mechanical properties and failure patterns of sandstone have been the common research focus of various disciplines integrating mechanics, material science, and engineering [6,7].…”
Section: Introductionmentioning
confidence: 99%